2010
DOI: 10.1021/ma102075c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mesophase Separation on the Crystallization Behavior of Olefin Block Copolymers

Abstract: This paper investigates the effect of mesophase separation on the crystallization behavior of olefin block copolymers (OBCs) with different octene contents, which were synthesized by chain shuttling technology. Crystallization always occurs simultaneously but competitively with mesophase separation in OBCs. Because of the reason that the crystallization temperature is lower than the mesophase separation temperature for the OBCs, the mesophase separation can start first; large portions of the crystallizable har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
94
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(104 citation statements)
references
References 20 publications
9
94
1
Order By: Relevance
“…Concerning possible future applications of DPD to studying the phase behavior of block copolymers we would like to mention, first of all, Markovian (random correlated) multiblock copolymers, a model that was deeply studied in theory since the seminal paper by Milner, Fredrickson, and Leibler 79 and recently attracted the attention of experimentalists [80][81][82] due to the progress in the controlled synthesis of multiblock polyolefins. 83 Comprehensive simulation techniques 84 reveal only short-range order in the disordered phase (microemulsion), which, however, possesses interesting mechanical characteristics, and it would be interesting to search for long-range ordered structures with the help of DPD.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning possible future applications of DPD to studying the phase behavior of block copolymers we would like to mention, first of all, Markovian (random correlated) multiblock copolymers, a model that was deeply studied in theory since the seminal paper by Milner, Fredrickson, and Leibler 79 and recently attracted the attention of experimentalists [80][81][82] due to the progress in the controlled synthesis of multiblock polyolefins. 83 Comprehensive simulation techniques 84 reveal only short-range order in the disordered phase (microemulsion), which, however, possesses interesting mechanical characteristics, and it would be interesting to search for long-range ordered structures with the help of DPD.…”
Section: Discussionmentioning
confidence: 99%
“…[29,31] The lamellae can be arranged into space-filling spherulites even when the crystallinity is as low as 7%, and the impinged spherulites show straight boundaries, which indicates that OBC experiences heterogeneous nucleation with nuclei of similar activity. [29,31,32] This morphology resembles crystallization from a miscible melt, and the phenomenon is distinct from that of traditional block copolymers. During crystallization, the aggregation of hard blocks forces segregation of the noncrystallizable soft blocks into the interlamellar regions.…”
Section: Introductionmentioning
confidence: 93%
“…Investigations have found that the block length, octene content as well as the ratio between hard and soft blocks is closely correlated to the apparent properties of this M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 promising elastomer. [33][34][35][36][37][38][39][40] In consideration of the difficulty of altering block architecture during synthesizing, we aim to adjust the apparent properties by blending with PE, which possesses architecture similar to hard blocks of OBC. Based on our exploration, we found that PE chains were inclined to cocrystallize with OBC, which made it possible to increase strength without great depression of tenacity.…”
Section: Introductionmentioning
confidence: 99%
“…Where only one of the monomers is crystallizable, such as in a study of poly(butylene terephthalate) (PBT)/poly(tetramethylene ether glycol), the other component may be rejected from crystals for small (in this case up to 17%) mole fraction, after which crystallization is suppressed . Other copolymer systems have shown crystallization by rejection of one component from the crystalline phase . However, in some cases of two, similar, crystallizing monomers, such as poly(ethylene terephthalate) (PET)/poly(ethylene 2,6‐naphthalate) (PEN) copolymers, crystallization involving both monomers may occur.…”
Section: Introductionmentioning
confidence: 99%